2012
DOI: 10.1155/2012/190901
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Quality of Life in Caregivers of People with Parkinson's Disease and Implications for Clinical Guidelines

Abstract: The quality of life (QoL) of informal caregivers can be adversely affected by a number of factors. This issue, however, has not been well explored for carers of people with Parkinson's (PwP), with research largely restricted to the assessment of caregiver burden and caregiver strain. This study aims to determine the main influences on carer QoL in this population and consider results in the context of current clinical guidelines for the management of Parkinson's disease (PD). Carers completed the newly validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 27 publications
6
42
0
4
Order By: Relevance
“…SF-36) and disease-specific measures (e.g. PDQ-39) and a relationship was revealed for three studies [21,26,43]. Martinez-Martin et al [25] did not find any relationships; however, PwP QoL was assessed by the carer using proxy measures.…”
Section: Quality Of Life and Other Outcomesmentioning
confidence: 95%
See 2 more Smart Citations
“…SF-36) and disease-specific measures (e.g. PDQ-39) and a relationship was revealed for three studies [21,26,43]. Martinez-Martin et al [25] did not find any relationships; however, PwP QoL was assessed by the carer using proxy measures.…”
Section: Quality Of Life and Other Outcomesmentioning
confidence: 95%
“…Details of the carer role, level of involvement or caring duties were rarely given. Only four studies [21][22][23][24] reported…”
Section: Design Setting Recruitment Strategies and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly many respondents among the PD relatives seemed to be adjusted and well-functioning in daily life, have resources left, be able to move on with their lives, and plan for the future. Also, lack of interest with daily news and activities was sparsely reported, which may tell us that sacrifice and other feelings of burden around the disease concomitants either were withheld or did not come through as in other studies (7,12,26). Possibly this says that many of responders in our study had good insight, were accommodated to the situation, found help in the support groups, and after all had the energy and mental prerequisites to follow their relatives' further struggles.…”
Section: Discussionmentioning
confidence: 61%
“…For a long time, PD has been primarily considered as a motor disorder, but in the last decades, several studies have highlighted the importance of cognitive symptoms and their impact on the quality of life of the patients and their caregivers 1 2. That is why the identification of predictors of evolution to dementia in PD (PDD) must be a key research priority.…”
Section: A Correlation Between the Neuroanatomical–neuropsychologicalmentioning
confidence: 99%